Geoinformacijska podpora upravljanju z nepremičninami - Ravnihar, Franc (Geodetski vestnik, 1997)
The paper outlines the ONIX project and within its framework a subproject entitled Geoinformation Support to Real Estate Management. The basic starting points, purpose and goals of the subproject and the usefulness of the system for real estate management are listed. The work program for implementing the second phase of the subproject is also presented.
Keywords: geodezija; nepremičnine; prostorski podatki; upravljanje